Geometric Morphometric Analysis and Gill Raker Count Variation of Populations of the Endemic Philippine Silver Perch, Leiopotherapon plumbeus (Perciformes Terapontidae) - Santos, Brian S.; Fontanilla, Ian Kendrich C.; Quilang, Jonas P. (2010)
Geometric morphometrics has been applied in various studies to determine shape variation in fish populations. In this study, landmark-based geometric morphometrics was used to examine shape variation in native and translocated populations of Leiopotherapon plumbeus (Kner, 1864), an endemic and economically important fish in the Philippines. A total of 844 specimens were collected from seven localities, namely, Laguna de Bay (Binangonan and Tanay areas), Sampaloc Lake, Taal Lake, Paoay Lake, Maasin River in Candaba Swamp, and Lake Buhi. L. plumbeus in Taal Lake, Sampaloc Lake and Lake Buhi were transplanted from Laguna de Bay, whereas those in Laguna de Bay, Paoay Lake and Maasin River were native to these areas. Shape variation in the samples was greatest in the head, followed by the body depth. Specimens from the Binangonan and Tanay areas of Laguna de Bay were the most similar morphologically. Specimens from Paoay Lake were the most distinct which could be due to the geographic isolation of L. plumbeus in this lake from all the other populations. Variation in gill raker count, the most discriminating meristic trait in a previous study, was also determined. Specimens from Binangonan and Tanay had the most number of gill rakers, whereas those from Paoay had the least. Variations in body shape and gill raker counts could be due to differences in feeding lifestyles in different habitats as well as differences in physico-chemical characteristics of the water bodies. Further studies are needed, however, to verify these findings and to determine the physico-chemical as well as genetic factors that could have contributed to such variation.
Keywords: Fish culture and the environment